Using soil ATP contents as bioindicator for paddy soil impacted by fluazinam applications - Fuzi Suciati; Dwindrata Basuki Aviantara (Journal of Multidisciplinary Academic, 2020)
Application of fluazinam, a pyridine-based fungicide, and its potential impact on the level of soil microbial biomass of paddy soils as estimated through soil ATP contents has been assessed. Soil ATP has been known to strongly correlated with soil microbial activity as such providing an indication of living soil microorganisms that mediating soil microbially active processes. To evaluate the effects of fluazinam, have on the levels of soil ATP a laboratory experiment was set up. Fluazinam at rate 3000 mg/kg was applied to air dried soils. Then following 1st, 3rd, 7th, and 14th-day of incubation the soil ATP contents were assessed. The levels of soil ATP were evaluated based on the emitted fluorescence intensities of oxyluciferin measured at a wavelength range 550 – 570 nm. Constantly decreasing level of soil ATP was detected throughout two weeks of experimental period, from 0.100 ± 0.006 to 0.043 ± 0.009 nmol/g soil. These finding suggested that fluazinam might induce deleterious effects to soil health and soil quality and might draw concern on environmental problems